Boosting the performance in steam electrolysis of solid oxide electrolysis cell by potassium-doping in Sr₂Fe₁.₅Mo₀.₅O₆-δ cathode - Li, Hao-Yang (2023)
Doping potassium ions (K+) in Sr2Fe1.5Mo0.5O6-δ (SFMO) double perovskite is shown to improve the electrocatalytic activity on hydrogen evolution reaction (HER) in solid oxide electrolysis cells (SOECs). The K+ dopant replaces the A-site strontium ion (Sr2+) in Sr2Fe1.5Mo0.5O6-δ and causes charge imbalance that induced the formation of positively charged defects within Sr2Fe1.5Mo0.5O6-δ and facilitates electrochemical processes in steam electrolysis. The enhanced processes include charge transfer, rate-determining oxide transport and surface hydrogen migration, and steam-dependent water adsorption reactions. Electrochemical impedance spectroscopy results evidently show: (1) Improvement in water adsorption reaction in K0.15Sr1.85Fe1.5Mo0.5O6-δ (K0.15SFMO) due to increase oxygen vacancy concentration for steam electrolysis.(2) The polarization resistance of the cell using K0.15Sr1.85Fe1.5Mo0.5O6-δ decreased by 50% compares to the cell using the Sr2Fe1.5Mo0.5O6-δ electrode.